Preclinical assessment of a modified Occlutech left atrial appendage closure device in a porcine model - Markus Reinthaler (Nature Portfolio, 2021)
Abstract Left atrial appendage (LAA) closure is being developed as an alternative for stroke prevention in patients with atrial fibrillation that cannot tolerate long-term oral anticoagulation. To assess the feasibility, safety, and performance of a novel modified Occlutech LAA closure device in a preclinical porcine model, the modified Occlutech modified Occlutech Plus LAA closure device was implanted in 12 female pigs (25–39 kg body weight) under fluoroscopic and transesophageal echocardiography (TEE) guidance. Procedural and technical success, as well as safety of LAA closure, were evaluated peri-procedurally and after 4, 8, and 12 weeks. Moreover, after 4, 8 and, 12 weeks animals were sacrificed for pathological analysis (e.g., thrombus formation, device ingrowth, endothelialization, and inflammation). All LAA closure devices were successfully implanted. On follow-up, no serious adverse events such as device-associated thrombus or translocalization/embolization were observed. A clinically non-significant pericarditis was observed in 4 animals at the time of autopsy. Endothelialization of the device was visible after 4 weeks, advanced after 8 weeks and completed after 12 weeks. Immunohistochemistry showed low amounts of inflammatory infiltration on the edges of the device. The results of this study indicate that implantation of a modified Occlutech LAA closure device is feasible with rapid endothelialization and low inflammatory infiltration in a porcine model. Human data are needed to further characterize safety and efficacy.